Insights into Online Education: Examining UG Students' Perceptions - Anirudha Jena (Journal of Hypermedia & Technology-Enhanced Learning, 2024)
This study explores undergraduate (UG) students’ perceptions of online classes at Buxi Jagabandhu Bidyadhar (BJB) Autonomous College, Odisha, India, during the COVID-19 pandemic. Using a descriptive survey methodology, 270 6th-semester students from various streams were selected through disproportionate stratified random sampling. The study analyzes differences in perception based on locality, gender, and academic stream, revealing statistically significant variations in their views on online learning. These insights are crucial for educators and policymakers seeking to overcome the challenges of remote education and to tailor online teaching practices to meet diverse student needs. The study contributes to the growing body of literature on online education by providing evidence-based recommendations for enhancing the UG learning experience in virtual environments.